Use of Innovative Technologies Through Teaching Mother Tongue Lessons and Use of Information Technologies During the Lesson Process - Nilufar Saitova (Zien Journals, 2022)
In this article, the use of innovative technologies in the teaching of mother tongue, increasing interest in the use of interactive methods in the educational process, pedagogical and information technology in the teaching process, the process of teaching the mother tongue a number of current problems and shortcomings awaiting their proof in terms of formulation are described in detail.
Keywords: information technology; innovative technologies; methodological support; interactive methods